Dyspnea, Dysphonia, and Cough: Varied Presentations of Tracheobronchopathia Osteochondroplastica. (October 2015) - Nielsen, Skyler W.; Stevens, Jayne R.; Dion, Gregory R.; Howard, N. Scott
Objectives: Tracheobronchopathia osteochondroplastica (TPO) is an uncommon, benign disease consisting of submucosal, osteocartilaginous nodules that project into the tracheal lumen. Far less commonly, these nodules can occur outside the tracheal cartilage. This case series discusses the wide range of symptoms and treatments of the disease. Methods: Three patients presented to the laryngology clinic with 3 varied presentations of TPO, including dyspnea, dysphonia, and cough. These patients were evaluated, subsequently diagnosed with TPO, and treated accordingly. Results: Two of the 3 patients presented with extratracheal lesions presenting in the cricoid and thyroid cartilages. The patient presenting with symptoms of dysphonia was found to have bilateral TPO exclusively within the thyroid cartilage, which has never been reported previously. After undergoing a partial thyroid cartilage resection removing the bulk of the lesion, the patient's symptoms drastically improved. Conclusion: While TPO may be a rare diagnosis in the general otolaryngologist practice, symptoms frequently bring patients into the otolaryngologist's clinic, and an awareness of the disease can help minimize unnecessary interventions and allow the surgeon to appropriately counsel patients.